Beyond essentiality: silicon as a systems regulator of photosynthesis under stress scenarios - Mukarram, Mohammad; Zehra, Andleeb; Afzal, Shadma; Sliacka Konôpková, Alena; Khan, Khalid Ali; Alqahtani, Abdulaziz R.; El-Mekkawy, Haitham Ibrahim; Kurjak, Daniel; Lux, Alexander; Chen, Rizhao; Li, Qiyun (Frontiers in Plant Science, 2026)
Silicon (Si), although not classified as an essential element, has emerged as a key modulator of photosynthesis and stress resilience in higher plants. However, despite extensive reports on its beneficial effects, a clear mechanistic understanding of how Si modulates photosynthetic machinery under stressful environments remains fragmented and inconsistent. This review critically synthesises recent advances in Si-mediated regulation of photosynthesis under both optimal and stress conditions. We highlight its influence on chlorophyll stability, photosystem (PSII/PSI) efficiency, electron transport, stomatal conductance, and nutrient homeostasis. We emphasise Si’s interaction with phytohormones and signalling molecules, including abscisic acid (ABA), nitric oxide (NO), and reactive oxygen species (ROS), which integrate hormonal and redox regulation of guard cell function. Emerging multi-omics studies and silicon nanoparticles (SiNPs) reveal how Si alters transcriptional networks, protein stability, and metabolite balance to sustain photosynthetic performance. This review addresses the knowledge gap in connecting Si-driven nutrient regulation with photosynthetic resilience by bridging omics approaches, hormonal crosstalk, and nanotechnology interventions. We conclude that strategic Si supplementation can be a sustainable approach to strengthen plant photoproductivity under climate change scenarios.